2020
DOI: 10.1155/2020/8857300
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Torsion in an Elderly Woman Associated with Leiomyoma and Continuously Elevating Muscle Enzymes: A Case Study and Review of Literature

Abstract: Uterine torsion is extremely rare in postmenopausal women. Total ischemia of the uterus may cause life-threatening conditions; hence, accurate diagnosis and surgical intervention are crucial. However, preoperative diagnosis is often challenging due to nonspecific clinical features and laboratory findings. We report a case of uterine torsion in a 73-year-old woman who presented with mild but gradually worsening intermittent abdominal pain. During a 5-day observation, repeated blood exams showed elevating serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…A previous report suggested that peritoneal signs are frequently absent in patients aged ⩾60 years. 21 However, our review revealed that peritoneal signs were also frequently absent in cases involving premenarcheal or young menstruating women ( Table 1 ). Regarding laboratory data, there are currently no known biomarkers that specifically indicate uterine torsion.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A previous report suggested that peritoneal signs are frequently absent in patients aged ⩾60 years. 21 However, our review revealed that peritoneal signs were also frequently absent in cases involving premenarcheal or young menstruating women ( Table 1 ). Regarding laboratory data, there are currently no known biomarkers that specifically indicate uterine torsion.…”
Section: Discussionmentioning
confidence: 89%
“…A case exhibiting gradual elevation of lactate dehydrogenase and creatinine phosphokinase levels after the onset of symptoms has been reported. 21 Similarly, there is a reported case wherein the patient developed coagulopathy. 10 However, these findings were not common in uterine torsion based on our review of recent cases (Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Uterine torsion is a rare gynecological emergency. Risk factors include structural anomalies that distort pelvic anatomy, such as pregnancy, uterine fibroids [4], ovarian cysts [5] and adnexal tumors, and ligamentous laxity in the pelvis [6,7]. Presentation is variable and often includes non-specific features, ranging from intermittent abdominal pain to acute deterioration with hemodynamic instability [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…increasing the risk of uterine torsion include structural anomalies that distort pelvic anatomy, such as pregnancy, uterine fibroids [4], ovarian cysts [5], and adnexal tumors, and ligamentous laxity in the pelvis [6,7]. Multiple case reports have described torsion either in the gravid uterus [2,6] or in postmenopausal women [7][8][9], yet rarely in the non-gravid, premenopausal uterus. To the best of our knowledge, there remains only a single case of uterine torsion in a premenopausal non-gravid woman in the literature, described in 1935 [1].…”
Section: Case Report Peer Reviewed | Open Access Wwwijcriogcommentioning
confidence: 99%